Meso-level contextual patterns of fathers' family leave uptake in Finland - Chapman Simon; Kotimäki Sanni; Helske Satu (Turun yliopisto, 2022)
Family leave uptake by fathers represents one pathway to redress the typically unequal division of early childcare, which has been linked to various family outcomes, including the mother’s employment and children’s schooling. The generous Nordic leave systems are designed around this concept to encourage  leave uptake, though the choice to take leave remains an individual one. There is a substantial body of literature on policy and individual-level drivers of leave uptake, but less so for meso-level factors, such as workplace and extended family, despite a possible key role in influencing individual family leave decisions. We used population register data from Finland to examine the demographics of fathers’ family leave uptake in 2007–2016. We found that uptake was highest amongst the employed, and that female-dominated industries and workplaces were associated with fathers taking longer periods of leave, particularly in the later years of the study. We also found possible indicators of role model effects, with long leaves of close family and of colleagues associated with longer leaves for new fathers. Our results suggest that meso-level contexts may be an important mediator in decisions surrounding uptake and length of fathers’ family leaves.